THE IMPLEMENTATION OF PLASTIC INJECTION MOLDING INDUSTRY IN ENHANCING INMATES' LIFE SKILLS AT CIKARANG CLASS IIA CORRECTIONAL FACILITY - Taqiyuddin, Zaki Difa; Soge, Markus Marselinus (Universitas Nusa Cendana, 2025)
The abstract provided discusses a study focused on the implementation of the Plastic Injection Molding industry at Lapas Kelas IIA Cikarang, which serves as a structured program designed to improve the life skills of inmates. By offering both technical training and direct work opportunities within the industrial sector, the initiative seeks to rehabilitate inmates by equipping them with practical, employable skills that they can apply after completing their sentences. This aligns with the broader goals of reintegration and reducing recidivism by providing inmates with tangible competencies that increase their chances of securing employment and reintegrating successfully into society. The study employs a qualitative research method, incorporating data gathered through in-depth interviews with key stakeholders, such as inmates, prison staff, and industry partners, alongside direct field observations of the program's operations. The findings of the research indicate that the program has been largely successful in imparting valuable technical skills to the inmates involved. However, the study also highlights several ongoing challenges, particularly in terms of limited equipment availability, which restricts the number of participants, and varying levels of inmate engagement, where some inmates are less motivated to fully commit to the program. Despite these challenges, the initiative has proven to play a vital role in the overall rehabilitation process, contributing significantly to the inmates' readiness for reintegration. The program not only provides them with the technical know-how needed for future employment in industries such as plastics manufacturing but also fosters a sense of responsibility, discipline, and teamwork. Overall, the Plastic Injection Molding program at Lapas Kelas IIA Cikarang demonstrates its potential to support both the personal development of inmates and the broader goals of correctional rehabilitation. Keywords: Plastic Injection Molding; Correctional Facility; Inmates Life Skills